2014
DOI: 10.22495/cocv12i1p2
|View full text |Cite
|
Sign up to set email alerts
|

Regional tax compliance and tax motivated earnings management: evidence from the 2008 Italian tax reform

Abstract: Using a large sample of public and private Italian companies, I investigate whether regional tax compliance affects earnings management activity in response to a decrease in the corporate tax rate. I find evidence that the higher the regional tax compliance where the company is based, the less managers engage in tax motivated earnings management. On the other hand, empirical results do not support the hypothesis that companies with an audit committee manage their earnings less in order to reduce their tax burd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Thus, research hypothesis H1 is confirmed, consistent with the findings of previous studies (e.g. Watrin et al, International Journal of Accounting and Financial Reporting ISSN 2162-3082 2019 2012; Lin et al, 2014;Mattei, 2014a;Mattei, 2014b;Sundvik, 2016;Höglund & Sundvik, 2016;Sundvik, 2017a;Sundvik, 2017b;Sundvik, 2017c;Dobbins et al, 2018;Haga et al, 2019).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, research hypothesis H1 is confirmed, consistent with the findings of previous studies (e.g. Watrin et al, International Journal of Accounting and Financial Reporting ISSN 2162-3082 2019 2012; Lin et al, 2014;Mattei, 2014a;Mattei, 2014b;Sundvik, 2016;Höglund & Sundvik, 2016;Sundvik, 2017a;Sundvik, 2017b;Sundvik, 2017c;Dobbins et al, 2018;Haga et al, 2019).…”
Section: Resultssupporting
confidence: 90%
“…As specifically concerns the Italian setting, Mattei (2014a) and Mattei (2014b) investigated the phenomenon under consideration with reference to a previous corporate standard tax rate cut (2008). They found that private companies shifted earnings from FY 2007 to FY 2008, thus managing their earnings.…”
Section: The Relationship Between Private Companies and The Practice Of Shifting Profits From The Fiscal Year In Which The Corporate Stanmentioning
confidence: 99%
See 1 more Smart Citation